Response and Nonresponse Bias in Oral Health Surveys - David Locker, PhD (Blackwell Synergy, 2000)
Oral health surveys are undertaken to provide estimates of the dental health and behaviors of populations or population subgroups. However, the integrity of the data from sample surveys may be compromised by one or more sources of sampling and nonsampling error